Math, asked by sitaram41978, 2 months ago

factorise 6abc - 9a²c​

Answers

Answered by CopyThat
12

Answer:

  • 3ac(-3a + 2b) is the factorized value.

Step-by-step explanation:

Given :

6abc - 9a²c

To find :

Factorized value.

Solution :

  • 6abc - 9a²c

⇒ -9a²c + 6abc

⇒ 3ac(-3a + 2b)

The factorized value is 3ac(-3a + 2b).

Verification :

  • 3ac(-3a + 2b)

⇒ 3ac(-3a) + 3ac(2b)

⇒ -9a²c + 6abc

⇒ 6abc - 9a²c

Answered by Anonymous
2

Answer:

-9a²c + 6abc

3ac(-3a + 2b)

Step-by-step explanation:

Similar questions